THE INDISPENSABLE ROLE OF PARENTS IN GUIDING THEIR CHILDREN TOWARDS FINDING A TRUE JOB AND BUILDING A MEANINGFUL CAREER - Maxsudova Behruzabonu; Egamberdiyeva Irodaxon Abdurahimovna (Лучшие интеллектуальные исследования, 2023)
Abstract:This article delves into the pivotal role that parents play in guiding their children towards finding a true job that aligns with their skills and passions, while also nurturing their career development. It emphasizes the influence of parental support, mentorship, and encouragement in empowering their children to pursue a fulfilling and purposeful career path.